Ti / Al composite electrode foil, manufacturing method and electrolytic capacitor
Through surface pretreatment and plasma deposition technology, the titanium film is formed, and combined with the use of hot pressing and self-assembly solution, the problem of poor bonding between titanium and aluminum in Ti/Al composite electrode foil is solved, significantly improving the stability and reliability of the electrode foil.
Patent Information
- Application Number
- CN202411405648.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-10
AI Technical Summary
In the Ti/Al composite electrode foil, the interface bond between titanium and aluminum is poor, which affects the performance and reliability of the electrode foil.
The titanium film was deposited by surface pretreatment of aluminum foil and titanium/aluminum composite sheets by plasma-enhanced chemical vapor deposition technology, and the binding strength was enhanced using a self-assembly solution during the hot pressing process, and finally the Ti/Al composite electrode foil was formed by hot pressing.
A firm titanium and aluminum interface is formed, which improves the stability and reliability of the electrode foil and reduces stress concentration and performance degradation due to performance mismatch.
Smart Images

Figure CN119153235B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrode foil manufacturing, and in particular to a Ti / Al composite electrode foil, a manufacturing method and an electrolytic capacitor. Background Art
[0002] Benefiting from the rapid development of the electronics, automobile, and new energy industries, the market size of electrolytic capacitors continues to grow and demand continues to expand.
[0003] Electrode foil is a key basic material for the production of electrolytic capacitors. It is used to carry charge. Its performance determines the key technical indicators of electrolytic capacitors, such as capacity, leakage current, loss, life, reliability, and volume. The commonly used electrode foil is aluminum electrode foil, which is processed by reprocessing conventional raw aluminum to achieve a purity of 99.93~99.9999% (6N). After a series of rolling, cleaning, and cutting processes, electronic aluminum foil is obtained. However, the current aluminum electrode foil has problems such as low capacity, large leakage current, poor temperature-frequency characteristics, and short service life. Therefore, the development of new aluminum alloy materials or composite materials to improve the specific capacitance and corrosion resistance of electrode foil has become a common improvement method. Among them, Ti / Al composite electrode foil has higher strength and hardness, and its mechanical properties have been significantly improved compared with single aluminum electrode foil.
[0004] However, the physical and chemical properties of titanium and aluminum are quite different, and poor interface bonding is prone to occur during the composite process, affecting the performance and reliability of the composite electrode foil. Summary of the invention
[0005] The present application provides a Ti / Al composite electrode foil, a manufacturing method and an electrolytic capacitor to solve the problem in the related art that the interface bonding between titanium and aluminum in the Ti / Al composite electrode foil is poor, which affects the performance of the composite electrode foil.
[0006] In a first aspect, a method for manufacturing a Ti / Al composite electrode foil is provided, comprising the following steps:
[0007] S1. Surface pretreatment: After cleaning the aluminum foil with a cleaning solution, immerse it in a 5-10wt% dilute hydrochloric acid solution for 5-10 minutes to obtain a pretreated aluminum foil, wherein the thickness of the aluminum foil is 10-15 μm;
[0008] S2. Composite sheet synthesis:
[0009] S201, mixing titanium powder and aluminum powder in a mass ratio of 3:7, adding magnesium powder accounting for 1-5% of the total mass of the titanium powder and the aluminum powder, inducing a self-propagating high temperature synthesis reaction in a ceramic crucible, and obtaining a Ti / Al composite material, wherein the particle sizes of the titanium powder, the aluminum powder and the magnesium powder are 10-50 μm;
[0010] S202, processing the Ti / Al composite material into a composite material sheet with a thickness of 50-100 μm;
[0011] S3, performing plasma enhanced chemical vapor deposition on the composite material sheet:
[0012] S301, placing the composite material sheet in a reaction chamber, starting the vacuum system, and evacuating the reaction chamber to an initial vacuum degree of 10 -3 Pa;
[0013] S302, using titanium tetrachloride and nitrogen as reaction gases, hydrogen as auxiliary gas, turning on the radio frequency plasma source, adjusting the radio frequency power to 100-500 W, adjusting the pressure in the reaction chamber to 5 Pa, depositing for 0.5-1 h, cooling to obtain a composite material sheet deposited with a titanium thin film, the titanium tetrachloride flow rate is 10-20 sccm, the nitrogen flow rate is 50-100 sccm, the hydrogen flow rate is 5-10 sccm, and the deposition temperature is 150-250°C;
[0014] S4, immersing the pretreated aluminum foil obtained in S1 and the composite material sheet deposited with a titanium thin film obtained in S3 in a self-assembly agent solution with a concentration of 1-5wt%, immersing for 0.5-1h, and drying at 80-100°C to obtain an impregnated aluminum foil and an impregnated composite material sheet, wherein the self-assembly agent solution is selected from an ethanol solution of 3-mercaptopropyltrimethoxysilane;
[0015] S5. Composite bonding: Place the impregnated aluminum foil and the impregnated composite material sheet in a hot press for 1 to 2 hours to obtain a Ti / Al composite electrode foil, wherein the impregnated aluminum foil is opposite to a side of the impregnated composite material sheet on which a titanium layer is deposited, and the hot pressing temperature is 350 to 450° C. and the pressure is 10 to 20 MPa.
[0016] Preferably, the cleaning solution comprises an ethanol solution and a sodium hydroxide solution, the concentration of the ethanol solution is 50-70wt%, the concentration of the sodium hydroxide solution is 1-3mol / L, and the volume ratio of the ethanol solution to the sodium hydroxide solution is 3:1-5:1.
[0017] Preferably, before S202 and after S201, the Ti / Al composite material is further subjected to hot isostatic pressing:
[0018] The Ti / Al composite material is placed in a pressure vessel of a hot isostatic pressing device, and the pressure vessel is evacuated to 10 -3 Pa, and filled with argon to 10 MPa;
[0019] The hot isostatic pressing equipment is started, the temperature is increased from the initial state of room temperature to the set temperature at a rate of 5-10°C / min, the pressure is increased from the initial state of 10 MPa to the set pressure at a rate of 1 MPa / min, and maintained at the set temperature and set pressure for 0.5-2h, and then the temperature and pressure are reduced at the same rate to the initial state to complete the hot isostatic pressing treatment of the Ti / Al composite material, the set temperature is 500-700°C, and the set pressure is 100-150 MPa.
[0020] Preferably, in step S3, before S301, the following steps are further included:
[0021] The composite material sheet was cleaned by ultrasonic wave, immersed in a 5-10 wt % dilute hydrochloric acid solution for 5-10 min, rinsed with deionized water, and dried with nitrogen.
[0022] Preferably, after S2, it further comprises depositing aluminum oxide on the composite material sheet:
[0023] The composite material sheet is placed in a reaction chamber, the vacuum system is started, and the reaction chamber is evacuated to an initial vacuum degree of 10 -3 Pa;
[0024] Using trimethylaluminum and oxygen as reaction gases, turning on the RF plasma source, adjusting the RF power to 250 W, adjusting the pressure in the reaction chamber to 3 Pa, and completing the alumina deposition on the composite material sheet after deposition for 0.5 to 1 hour. The trimethylaluminum flow rate is 5 to 20 sccm, and the oxygen flow rate is 30 to 60 sccm.
[0025] Preferably, the titanium film is deposited on the side of the composite material sheet on which the aluminum oxide is deposited.
[0026] Preferably, in S302, the deposition temperature is increased step by step, the initial deposition temperature is 190-220°C, and the temperature is increased at a rate of 1°C / min until it reaches 250°C.
[0027] In a second aspect, a Ti / Al composite electrode foil is provided, which is manufactured by any of the above-mentioned methods for manufacturing a Ti / Al composite electrode foil.
[0028] In a third aspect, an electrolytic capacitor is provided, which uses the Ti / Al composite electrode foil as described above as an electrode.
[0029] The beneficial effects of the technical solution provided by this application include:
[0030] The present application provides a Ti / Al composite electrode foil, a manufacturing method and an electrolytic capacitor. The aluminum foil and the Ti / Al composite material are hot-pressed and a titanium film is manufactured between the two by plasma enhanced chemical vapor deposition. The titanium film serves as an intermediate layer and has good chemical stability and mechanical strength. It can promote atomic diffusion during the hot-pressing process to form a strong bonding interface. It can also serve as a barrier layer to prevent mutual diffusion and chemical reaction between the aluminum foil and the Ti / Al composite material, reduce stress concentration and performance degradation caused by performance mismatch, and improve the stability and reliability of the Ti / Al composite electrode foil. Before hot-pressing, the aluminum foil and the Ti / Al composite material sheet with the titanium film deposited thereon are immersed in a self-assembly agent solution. The monomolecular layer formed on the surface of the material by the self-assembly agent solution strengthens the bonding strength and effectively forms a strong composite structure. Therefore, the problem of poor bonding between the titanium and aluminum interfaces in the Ti / Al composite electrode foil in the related art, which affects the performance of the composite electrode foil, can be solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 The present invention provides a flow chart of the method for manufacturing the Ti / Al composite electrode foil. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0034] See also Figure 1 As shown, the present invention provides a method for manufacturing a Ti / Al composite electrode foil, which can solve the problem in the related art that the interface between titanium and aluminum in the Ti / Al composite electrode foil is poorly bonded, affecting the performance of the composite electrode foil. The manufacturing method comprises the following steps:
[0035] S1. Surface pretreatment: After cleaning the aluminum foil with a cleaning solution, immerse it in a 5-10 wt % dilute hydrochloric acid solution for 5-10 min to obtain a pretreated aluminum foil, wherein the thickness of the aluminum foil is 10-15 μm.
[0036] In some embodiments, the cleaning solution includes an ethanol solution and a sodium hydroxide solution, the concentration of the ethanol solution is 50-70 wt %, the concentration of the sodium hydroxide solution is 1-3 mol / L, and the volume ratio of the ethanol solution to the sodium hydroxide solution is 3:1-5:1.
[0037] S2. Composite sheet synthesis:
[0038] S201, mixing titanium powder and aluminum powder in a mass ratio of 3:7, adding magnesium powder accounting for 1-5% of the total mass of the titanium powder and the aluminum powder, inducing a self-propagating high temperature synthesis reaction in a ceramic crucible, and obtaining a Ti / Al composite material, wherein the particle sizes of the titanium powder, the aluminum powder and the magnesium powder are 10-50 μm;
[0039] S202, processing the Ti / Al composite material into a composite material sheet with a thickness of 50-100 μm.
[0040] In some embodiments, before S202 and after S201, the Ti / Al composite material is further subjected to hot isostatic pressing:
[0041] The Ti / Al composite material is placed in a pressure vessel of a hot isostatic pressing device, and the pressure vessel is evacuated to 10 -3 Pa, and filled with argon to 10 MPa;
[0042] The hot isostatic pressing equipment is started, the temperature is increased from the initial state of room temperature to the set temperature at a rate of 5-10°C / min, the pressure is increased from the initial state of 10MPa to the set pressure at a rate of 1 MPa / min, and maintained at the set temperature and set pressure for 0.5-2h, and then the temperature and pressure are reduced to the initial state at the same rate to complete the hot isostatic pressing treatment of the Ti / Al composite material, the set temperature is 500-700°C, and the set pressure is 100-150MPa.
[0043] Specifically, after hot isostatic pressing treatment, the microstructure of the Ti / Al composite material becomes denser and more uniform, effectively eliminating internal pores and defects, which helps to improve the mechanical properties, corrosion resistance and conductivity, making it more suitable as an electrode foil material; under high temperature and high pressure conditions, titanium and aluminum atoms can further diffuse and combine to form a more solid interface to enhance the bonding strength and integrity of the Ti / Al composite material.
[0044] S3, performing plasma enhanced chemical vapor deposition on the composite material sheet:
[0045] S301, placing the composite material sheet in a reaction chamber, starting the vacuum system, and evacuating the reaction chamber to an initial vacuum degree of 10 -3 Pa;
[0046] S302, titanium tetrachloride and nitrogen are used as reaction gases, hydrogen is used as auxiliary gas, the radio frequency plasma source is turned on, the radio frequency power is adjusted to 100-500 W, the pressure in the reaction chamber is adjusted to 5 Pa, and after deposition for 0.5-1h, cooling is performed to obtain a composite material sheet deposited with a titanium film, the titanium tetrachloride flow rate is 10-20 sccm, the nitrogen flow rate is 50-100 sccm, the hydrogen flow rate is 5-10 sccm, and the deposition temperature is 150-250° C. The reaction gas is fully decomposed and deposited to form a uniform film, and the titanium film obtained by plasma enhanced chemical vapor deposition has high purity and uniformity, which can improve the surface properties of the electrode foil.
[0047] In some embodiments, in S302, the deposition temperature is increased step by step, the initial deposition temperature is 190-220°C, and the temperature is increased at a rate of 1°C / min until it reaches 250°C.
[0048] In some embodiments, before S301, the method further includes:
[0049] The composite material sheet was cleaned by ultrasonic wave, immersed in a 5-10 wt % dilute hydrochloric acid solution for 5-10 min, rinsed with deionized water, and dried with nitrogen.
[0050] In some embodiments, before S3 and after S2, it also includes the step of depositing aluminum oxide on the composite material sheet:
[0051] The composite material sheet is placed in a reaction chamber, the vacuum system is started, and the reaction chamber is evacuated to an initial vacuum degree of 10 -3 Pa;
[0052] Using trimethylaluminum and oxygen as reaction gases, turning on the RF plasma source, adjusting the RF power to 250 W, adjusting the pressure in the reaction chamber to 3 Pa, and completing the alumina deposition on the composite material sheet after deposition for 0.5 to 1 hour. The trimethylaluminum flow rate is 5 to 20 sccm, and the oxygen flow rate is 30 to 60 sccm.
[0053] Optionally, the titanium film is deposited on a side of the composite material sheet on which aluminum oxide is deposited.
[0054] Introducing a metal oxide intermediate layer between the titanium film and the Ti / Al composite sheet can improve the chemical compatibility and bonding strength between the two.
[0055] S4, immersing the pretreated aluminum foil obtained in S1 and the composite material sheet deposited with a titanium film obtained in S3 in a self-assembly agent solution with a concentration of 1-5wt%, immersing for 0.5-1h, and drying at 80-100°C to obtain an impregnated aluminum foil and an impregnated composite material sheet, wherein the self-assembly agent solution is selected from an ethanol solution of 3-mercaptopropyltrimethoxysilane. The self-assembly agent forms a uniform monomolecular layer on the surface of the material, firmly bonded to the surface of the pretreated aluminum foil and the composite material sheet deposited with a titanium film, and fully bonds the two in the subsequent hot pressing process to form a firm composite structure.
[0056] S5. Composite bonding: Place the impregnated aluminum foil and the impregnated composite material sheet in a hot press for 1 to 2 hours to obtain a Ti / Al composite electrode foil, wherein the impregnated aluminum foil is opposite to a side of the impregnated composite material sheet on which a titanium layer is deposited, and the hot pressing temperature is 350 to 450° C. and the pressure is 10 to 20 MPa.
[0057] Specifically, the titanium layer is located between the Ti / Al composite material and the aluminum foil. On the one hand, the titanium layer, as an intermediate layer, can enhance the bonding force between the aluminum foil and the Ti / Al composite material. Titanium has good chemical stability and mechanical strength, and can promote atomic diffusion during hot pressing to form a strong bonding interface; on the other hand, it matches the thermal expansion coefficient and electrical properties of the aluminum foil and the Ti / Al composite material, and acts as a barrier layer to prevent mutual diffusion and chemical reaction between the aluminum foil and the Ti / Al composite material, reduce stress concentration and performance degradation caused by performance mismatch, and improve the stability and reliability of the Ti / Al composite electrode foil.
[0058] Example 1
[0059] The method for manufacturing the Ti / Al composite electrode foil provided in this embodiment comprises the following steps:
[0060] S1. Surface pretreatment: After cleaning the aluminum foil with a cleaning solution, immerse it in a 5 wt % dilute hydrochloric acid solution for 10 min to obtain a pretreated aluminum foil, wherein the thickness of the aluminum foil is 15 μm;
[0061] The cleaning solution includes 70wt% ethanol solution and 1mol / L sodium hydroxide solution, and the volume ratio of the ethanol solution to the sodium hydroxide solution is 3:1.
[0062] S2. Composite sheet synthesis:
[0063] S201, 30 g of titanium powder with a particle size of 50 μm was mixed with 70 g of aluminum powder, and 1 g of magnesium powder was added to initiate a self-propagating high temperature synthesis reaction in a ceramic crucible to obtain a Ti / Al composite material, wherein the particle size of the titanium powder, aluminum powder and magnesium powder was 50 μm;
[0064] S202, processing the Ti / Al composite material into a composite material sheet with a thickness of 100 μm.
[0065] S3, performing plasma enhanced chemical vapor deposition on the composite material sheet:
[0066] S301, placing the composite material sheet in a reaction chamber, starting the vacuum system, and evacuating the reaction chamber to an initial vacuum degree of 10 -3 Pa;
[0067] S302. Use titanium tetrachloride and nitrogen as reaction gases and hydrogen as auxiliary gas, turn on the RF plasma source, adjust the RF power to 500 W, adjust the pressure in the reaction chamber to 5 Pa, and after deposition for 0.5 h, cool to obtain a composite material sheet deposited with a titanium thin film. The titanium tetrachloride flow rate is 10 sccm, the nitrogen flow rate is 50 sccm, the hydrogen flow rate is 5 sccm, and the deposition temperature is 250°C.
[0068] S4, immersing the pretreated aluminum foil obtained in S1 and the composite material sheet deposited with a titanium thin film obtained in S3 in a self-assembly agent solution with a concentration of 5wt%, immersing for 0.5h, and drying at 100°C to obtain an impregnated aluminum foil and an impregnated composite material sheet, wherein the self-assembly agent solution is selected from an ethanol solution of 3-mercaptopropyltrimethoxysilane;
[0069] S5. Composite bonding: Place the impregnated aluminum foil and the impregnated composite material sheet in a hot press and hot press for 1 hour to obtain a Ti / Al composite electrode foil, wherein the impregnated aluminum foil is opposite to a side of the impregnated composite material sheet on which a titanium layer is deposited, and the hot pressing temperature is 450° C. and the pressure is 10 MPa.
[0070] Example 2
[0071] The method for manufacturing the Ti / Al composite electrode foil provided in this embodiment comprises the following steps:
[0072] S1. Surface pretreatment: After cleaning the aluminum foil with a cleaning solution, immerse it in an 8 wt % dilute hydrochloric acid solution for 6 min to obtain a pretreated aluminum foil, wherein the thickness of the aluminum foil is 12 μm;
[0073] The cleaning solution includes 60wt% ethanol solution and 2mol / L sodium hydroxide solution, and the volume ratio of the ethanol solution to the sodium hydroxide solution is 3:1.
[0074] S2. Composite sheet synthesis:
[0075] S201, 30 g of titanium powder with a particle size of 20 μm was mixed with 70 g of aluminum powder, and 3 g of magnesium powder was added to initiate a self-propagating high temperature synthesis reaction in a ceramic crucible to obtain a Ti / Al composite material, wherein the particle size of the titanium powder, aluminum powder and magnesium powder was 20 μm;
[0076] The Ti / Al composite material is placed in a pressure vessel of a hot isostatic pressing device, and the pressure vessel is evacuated to 10 -3 Pa, and filled with argon to 10 MPa;
[0077] The hot isostatic pressing equipment was started, the temperature was increased from the initial state of room temperature (25°C) to the set temperature at a rate of 5°C / min, the pressure was increased from the initial state of 10 MPa to the set pressure at a rate of 1 MPa / min, and after maintaining the set temperature and set pressure for 1 hour, the temperature and pressure were reduced at the same rate to the initial state to obtain a Ti / Al composite material treated with hot isostatic pressing, the set temperature was 600°C, and the set pressure was 120 MPa.
[0078] S202, processing the Ti / Al composite material subjected to hot isostatic pressing into a composite material sheet with a thickness of 60 μm.
[0079] S3, performing plasma enhanced chemical vapor deposition on the composite material sheet:
[0080] The composite sheet was cleaned by ultrasonic wave, immersed in a 5 wt % dilute hydrochloric acid solution for 10 min, rinsed with deionized water, and dried with nitrogen.
[0081] S301, placing the cleaned and dried composite material sheet in a reaction chamber, starting the vacuum system, and pumping the reaction chamber to an initial vacuum degree of 10 -3 Pa;
[0082] S302. Use titanium tetrachloride and nitrogen as reaction gases and hydrogen as auxiliary gas, turn on the RF plasma source, adjust the RF power to 300 W, adjust the pressure in the reaction chamber to 5 Pa, and after deposition for 40 minutes, cool to obtain a composite material sheet deposited with a titanium thin film. The titanium tetrachloride flow rate is 15 sccm, the nitrogen flow rate is 80 sccm, the hydrogen flow rate is 8 sccm, and the deposition temperature is 200°C.
[0083] S4, immersing the pretreated aluminum foil obtained in S1 and the composite material sheet deposited with a titanium thin film obtained in S3 in a self-assembly agent solution with a concentration of 4wt%, immersing for 40 minutes, and drying at 90°C to obtain an impregnated aluminum foil and an impregnated composite material sheet, wherein the self-assembly agent solution is selected from an ethanol solution of 3-mercaptopropyltrimethoxysilane;
[0084] S5. Composite bonding: Place the impregnated aluminum foil and the impregnated composite material sheet in a hot press for 1.5 hours to obtain a Ti / Al composite electrode foil, wherein the impregnated aluminum foil is opposite to a side of the impregnated composite material sheet on which a titanium layer is deposited, and the hot pressing temperature is 400° C. and the pressure is 13 MPa.
[0085] Example 3
[0086] The method for manufacturing the Ti / Al composite electrode foil provided in this embodiment comprises the following steps:
[0087] S1. Surface pretreatment: After cleaning the aluminum foil with a cleaning solution, immerse it in a 10 wt % dilute hydrochloric acid solution for 5 min to obtain a pretreated aluminum foil, wherein the thickness of the aluminum foil is 10 μm;
[0088] The cleaning solution includes 70wt% ethanol solution and 3mol / L sodium hydroxide solution, and the volume ratio of the ethanol solution to the sodium hydroxide solution is 4:1.
[0089] S2. Composite sheet synthesis:
[0090] S201, 30 g of titanium powder with a particle size of 15 μm was mixed with 70 g of aluminum powder, and 5 g of magnesium powder was added to initiate a self-propagating high temperature synthesis reaction in a ceramic crucible to obtain a Ti / Al composite material, wherein the particle size of the titanium powder, aluminum powder and magnesium powder was 15 μm;
[0091] The Ti / Al composite material is placed in a pressure vessel of a hot isostatic pressing device, and the pressure vessel is evacuated to 10 -3 Pa, and filled with argon to 10 MPa;
[0092] The hot isostatic pressing equipment was started, the temperature was increased from the initial state of room temperature (25°C) to the set temperature at a rate of 8°C / min, the pressure was increased from the initial state of 10 MPa to the set pressure at a rate of 1 MPa / min, and after maintaining the set temperature and set pressure for 2 hours, the temperature and pressure were reduced at the same rate to the initial state to obtain a Ti / Al composite material treated with hot isostatic pressing, the set temperature was 700°C, and the set pressure was 100 MPa.
[0093] S202, processing the Ti / Al composite material subjected to hot isostatic pressing into a composite material sheet with a thickness of 50 μm.
[0094] The composite material sheet is placed in a reaction chamber, the vacuum system is started, and the reaction chamber is evacuated to an initial vacuum degree of 10 -3 Pa;
[0095] Using trimethylaluminum and oxygen as reaction gases, turning on the RF plasma source, adjusting the RF power to 250 W, adjusting the pressure in the reaction chamber to 3 Pa, and after deposition for 0.5 h, obtaining a composite material sheet with a deposited aluminum oxide intermediate layer, the trimethylaluminum flow rate was 20 sccm, and the oxygen flow rate was 60 sccm.
[0096] S3, performing plasma enhanced chemical vapor deposition on the composite material sheet with the aluminum oxide intermediate layer deposited thereon:
[0097] The composite sheet with the deposited aluminum oxide intermediate layer was cleaned by ultrasonic wave, immersed in a 10 wt % dilute hydrochloric acid solution for 5 min, rinsed with deionized water, and dried with nitrogen.
[0098] S301, placing the cleaned and dried composite sheet of the deposited aluminum oxide intermediate layer in a reaction chamber, starting the vacuum system, and pumping the reaction chamber to an initial vacuum degree of 10 -3 Pa;
[0099] S302. Use titanium tetrachloride and nitrogen as reaction gases and hydrogen as auxiliary gas, turn on the RF plasma source, adjust the RF power to 100 W, adjust the pressure in the reaction chamber to 5 Pa, and deposit the titanium film on the side where the aluminum oxide intermediate layer is deposited. After deposition for 1 hour, cool and obtain a composite material sheet deposited with the titanium film. The titanium tetrachloride flow rate is 20 sccm, the nitrogen flow rate is 100 sccm, the hydrogen flow rate is 10 sccm, and the deposition temperature is 190-250°C.
[0100] In S302, the deposition temperature is increased step by step. The initial deposition temperature is 190°C, and the temperature is increased at a rate of 1°C / min until it reaches 250°C.
[0101] S4, immersing the pretreated aluminum foil obtained in S1 and the composite material sheet deposited with a titanium thin film obtained in S3 in a self-assembly agent solution with a concentration of 1 wt%, immersing for 1 hour, and drying at 80° C. to obtain an impregnated aluminum foil and an impregnated composite material sheet, wherein the self-assembly agent solution is selected from an ethanol solution of 3-mercaptopropyltrimethoxysilane;
[0102] S5. Composite bonding: Place the impregnated aluminum foil and the impregnated composite material sheet in a hot press for 2 hours to obtain a Ti / Al composite electrode foil, wherein the impregnated aluminum foil is opposite to a side of the impregnated composite material sheet on which a titanium layer is deposited, and the hot pressing temperature is 350° C. and the pressure is 20 MPa.
[0103] Example 4
[0104] The method for manufacturing the Ti / Al composite electrode foil provided in this embodiment comprises the following steps:
[0105] S1. Surface pretreatment: After cleaning the aluminum foil with a cleaning solution, immerse it in a 6 wt % dilute hydrochloric acid solution for 6 min to obtain a pretreated aluminum foil, wherein the thickness of the aluminum foil is 12 μm;
[0106] The cleaning solution includes 50wt% ethanol solution and 2mol / L sodium hydroxide solution, and the volume ratio of the ethanol solution to the sodium hydroxide solution is 5:1.
[0107] S2. Composite sheet synthesis:
[0108] S201, 30 g of titanium powder with a particle size of 10 μm was mixed with 70 g of aluminum powder, and 4 g of magnesium powder was added to initiate a self-propagating high temperature synthesis reaction in a ceramic crucible to obtain a Ti / Al composite material, wherein the particle size of the titanium powder, aluminum powder and magnesium powder was 10 μm;
[0109] The Ti / Al composite material is placed in a pressure vessel of a hot isostatic pressing device, and the pressure vessel is evacuated to 10 -3 Pa, and filled with argon to 10 MPa;
[0110] The hot isostatic pressing equipment was started, and the temperature was increased from the initial state of room temperature (25°C) to the set temperature of 700°C at a rate of 10°C / min, and the pressure was increased from the initial state of 10 MPa to the set pressure of 100 MPa at a rate of 1 MPa / min. After maintaining the set temperature and set pressure for 0.5 h, the temperature and pressure were reduced at the same rate to the initial state to obtain the hot isostatic pressed Ti / Al composite material.
[0111] S202, processing the Ti / Al composite material subjected to hot isostatic pressing into a composite material sheet with a thickness of 80 μm.
[0112] The composite material sheet is placed in a reaction chamber, the vacuum system is started, and the reaction chamber is evacuated to an initial vacuum degree of 10 -3 Pa;
[0113] Using trimethylaluminum and oxygen as reaction gases, turning on the RF plasma source, adjusting the RF power to 250 W, adjusting the pressure in the reaction chamber to 3 Pa, and after deposition for 1 hour, obtaining a composite material sheet with a deposited aluminum oxide intermediate layer, the trimethylaluminum flow rate is 5 sccm, and the oxygen flow rate is 30 sccm.
[0114] S3, performing plasma enhanced chemical vapor deposition on the composite material sheet with the aluminum oxide intermediate layer deposited thereon:
[0115] The composite sheet with the deposited aluminum oxide intermediate layer was cleaned by ultrasonic wave, immersed in a 8 wt % dilute hydrochloric acid solution for 8 min, rinsed with deionized water, and dried with nitrogen.
[0116] S301, placing the cleaned and dried composite sheet of the deposited aluminum oxide intermediate layer in a reaction chamber, starting the vacuum system, and pumping the reaction chamber to an initial vacuum degree of 10 -3 Pa;
[0117] S302. Use titanium tetrachloride and nitrogen as reaction gases and hydrogen as auxiliary gas, turn on the RF plasma source, adjust the RF power to 200 W, adjust the pressure in the reaction chamber to 5 Pa, and deposit the titanium film on the side where aluminum oxide is deposited. After deposition for 50 minutes, cool and obtain a composite material sheet deposited with titanium film. The titanium tetrachloride flow rate is 15 sccm, the nitrogen flow rate is 70 sccm, the hydrogen flow rate is 6 sccm, and the deposition temperature is 200-250°C.
[0118] In S302, the deposition temperature is increased step by step. The initial deposition temperature is 200°C, and the temperature is increased at a rate of 1°C / min until it reaches 250°C.
[0119] S4, immersing the pretreated aluminum foil obtained in S1 and the composite material sheet deposited with a titanium thin film obtained in S3 in a self-assembly agent solution with a concentration of 2wt%, immersing for 0.5h, and drying at 85°C to obtain an impregnated aluminum foil and an impregnated composite material sheet, wherein the self-assembly agent solution is selected from an ethanol solution of 3-mercaptopropyltrimethoxysilane;
[0120] S5. Composite bonding: Place the impregnated aluminum foil and the impregnated composite material sheet in a hot press for 2 hours to obtain a Ti / Al composite electrode foil, wherein the impregnated aluminum foil is opposite to a side of the impregnated composite material sheet on which a titanium layer is deposited, and the hot pressing temperature is 350° C. and the pressure is 15 MPa.
[0121] Example 5
[0122] The method for manufacturing the Ti / Al composite electrode foil provided in this embodiment comprises the following steps:
[0123] S1. Surface pretreatment: After cleaning the aluminum foil with a cleaning solution, immerse it in an 8 wt % dilute hydrochloric acid solution for 6 min to obtain a pretreated aluminum foil, wherein the thickness of the aluminum foil is 10 μm;
[0124] The cleaning solution includes 65wt% ethanol solution and 1.5mol / L sodium hydroxide solution, and the volume ratio of the ethanol solution to the sodium hydroxide solution is 9:2. The cleaning solution covers the aluminum foil.
[0125] S2. Composite sheet synthesis:
[0126] S201, 30 g of titanium powder with a particle size of 15 μm was mixed with 70 g of aluminum powder, and 3 g of magnesium powder was added to initiate a self-propagating high temperature synthesis reaction in a ceramic crucible to obtain a Ti / Al composite material, wherein the particle size of the titanium powder, aluminum powder and magnesium powder was 15 μm;
[0127] S202, processing the Ti / Al composite material into a composite material sheet with a thickness of 60 μm.
[0128] The composite material sheet is placed in a reaction chamber, the vacuum system is started, and the reaction chamber is evacuated to an initial vacuum degree of 10 -3 Pa;
[0129] Using trimethylaluminum and oxygen as reaction gases, turning on the RF plasma source, adjusting the RF power to 250 W, adjusting the pressure in the reaction chamber to 3 Pa, and after deposition for 40 minutes, obtaining a composite material sheet with a deposited aluminum oxide intermediate layer, the trimethylaluminum flow rate is 10 sccm, and the oxygen flow rate is 40 sccm.
[0130] S3, performing plasma enhanced chemical vapor deposition on the composite material sheet with the aluminum oxide intermediate layer deposited thereon:
[0131] S301, placing the composite material sheet with the aluminum oxide intermediate layer deposited thereon in a reaction chamber, starting the vacuum system, and evacuating the reaction chamber to an initial vacuum degree of 10 -3 Pa;
[0132] S302. Use titanium tetrachloride and nitrogen as reaction gases and hydrogen as auxiliary gas, turn on the RF plasma source, adjust the RF power to 300 W, adjust the pressure in the reaction chamber to 5 Pa, and deposit the titanium film on the side where aluminum oxide is deposited. After deposition for 0.5 h, cool and obtain a composite material sheet deposited with titanium film. The titanium tetrachloride flow rate is 20 sccm, the nitrogen flow rate is 100 sccm, the hydrogen flow rate is 12 sccm, and the deposition temperature is 220-250°C.
[0133] In S302, the deposition temperature is increased step by step. The initial deposition temperature is 220°C, and the temperature is increased at a rate of 1°C / min until it reaches 250°C.
[0134] S4, immersing the pretreated aluminum foil obtained in S1 and the composite material sheet deposited with a titanium thin film obtained in S3 in a self-assembly agent solution with a concentration of 3wt%, immersing for 1 hour, and drying at 90°C to obtain an impregnated aluminum foil and an impregnated composite material sheet, wherein the self-assembly agent solution is selected from an ethanol solution of 3-mercaptopropyltrimethoxysilane;
[0135] S5. Composite bonding: Place the impregnated aluminum foil and the impregnated composite material sheet in a hot press for 1.5 hours to obtain a Ti / Al composite electrode foil, wherein the impregnated aluminum foil is opposite to a side of the impregnated composite material sheet on which a titanium layer is deposited, and the hot pressing temperature is 400° C. and the pressure is 15 MPa.
[0136] Comparative Example 1
[0137] The difference between the embodiment 1 and the embodiment 1 is that step S3 is not performed, and the pretreated aluminum foil obtained in step S1 and the composite material sheet obtained in step S2 are impregnated with the self-assembly agent solution in the original step S4 in embodiment 1; the other steps are the same as those in embodiment 1.
[0138] Comparative Example 2
[0139] The difference between the embodiment 1 and the embodiment 1 is that step S4 is not performed, and the composite bonding is performed directly; the other steps are the same as those in the embodiment 1.
[0140] Comparative Example 3
[0141] The difference between the embodiment 1 and the embodiment 1 is that, in step S1, deionized water is used as the cleaning liquid; the other steps are the same as those in the embodiment 1.
[0142] Comparative Example 4
[0143] The difference between this method and Example 1 is that the original steps S3 and S4 are not performed, and the pretreated aluminum foil obtained in S1 and the composite material sheet obtained in S2 are composited; the other steps are the same as those in Example 1.
[0144] The Ti / Al composite electrode foils manufactured in Examples 1 to 5 and Comparative Examples 1 to 4 were tested:
[0145] Tensile strength test:
[0146] The Ti / Al composite electrode foils manufactured in Examples 1 to 5 and Comparative Examples 1 to 4 were cut into rectangular specimens with a width of 20 mm and a length of 100 mm. The rectangular specimens were clamped along the length direction using a universal material testing machine and stretched at a stretching speed of 10 mm / min until the specimen broke. The force value and displacement data during the stretching process were recorded, and the tensile strength and elongation at break were calculated.
[0147] Bending strength test:
[0148] The Ti / Al composite electrode foils manufactured in Examples 1 to 5 and Comparative Examples 1 to 4 were cut into rectangular specimens with a width of 20 mm and a length of 100 mm. Using a three-point bending tester, the specimens were placed on two supporting points, and a downward force was applied in the middle of the specimen until the specimen broke. The force value and displacement data during the bending process were recorded, and the bending strength was calculated.
[0149] Electrode specific capacity test:
[0150] The Ti / Al composite electrode foils obtained in Examples 1 to 5 and Comparative Examples 1 to 4 were cut into 1 cm×1 cm squares and used as working electrodes. They were mounted on an electrode fixture and placed in an electrolytic cell. A calomel electrode was used as a reference electrode and a platinum electrode was used as a counter electrode. The potential range was set at -0.2 V to 0.8 V, the scan rate was set at 10 mV / s, and the electrochemical workstation was started to perform cyclic voltammetry tests. The response current of the electrode at different potentials was recorded.
[0151] The test was repeated 10 times to ensure the stability and repeatability of the test results.
[0152] According to the cyclic voltammetry curve, the electrode specific capacity is calculated using the following formula:
[0153]
[0154] Where C is the specific capacitance, ∫IdV is the integrated area of the cyclic voltammetry curve, v is the scan rate, and ΔV is the potential window.
[0155] The test results are shown in Table 1.
[0156] Table 1
[0157]
[0158] It can be seen that Examples 1 to 5 have stronger mechanical properties and higher electrode specific capacitance than Comparative Examples 1 to 4, and Examples 2 to 4 are better than Examples 1 and 5, mainly because the Ti / Al composite material has been subjected to hot isostatic pressing treatment, and the mechanical strength and bonding strength have been improved. In Example 3, a deposited intermediate layer of aluminum oxide is added, and the capacitance value is further improved.
[0159] The present application also provides a Ti / Al composite electrode foil, which is manufactured by any one of the manufacturing methods of the above-mentioned embodiments 1 to 5, and will not be described again.
[0160] The present application also provides an electrolytic capacitor, which uses any one of the electrode foils of the above embodiments 1 to 5 as an electrode.
[0161] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for manufacturing a Ti / Al composite electrode foil, characterized in that: It includes the following steps: S1. Surface pretreatment: After cleaning the aluminum foil with a cleaning solution, immerse it in a 5-10wt% dilute hydrochloric acid solution for 5-10 minutes to obtain a pretreated aluminum foil, wherein the thickness of the aluminum foil is 10-15 μm; S2. Composite sheet synthesis: S201, mixing titanium powder and aluminum powder in a mass ratio of 3:7, adding magnesium powder accounting for 1-5% of the total mass of the titanium powder and the aluminum powder, inducing a self-propagating high temperature synthesis reaction in a ceramic crucible, and obtaining a Ti / Al composite material, wherein the particle sizes of the titanium powder, the aluminum powder and the magnesium powder are 10-50 μm; S202, processing the Ti / Al composite material into a composite material sheet with a thickness of 50-100 μm; S3, performing plasma enhanced chemical vapor deposition on the composite material sheet: S301, placing the composite material sheet in a reaction chamber, starting the vacuum system, and evacuating the reaction chamber to an initial vacuum degree of 10 -3 Pa; S302, using titanium tetrachloride and nitrogen as reaction gases, hydrogen as auxiliary gas, turning on the radio frequency plasma source, adjusting the radio frequency power to 100-500 W, adjusting the pressure in the reaction chamber to 5 Pa, depositing for 0.5-1 h, cooling to obtain a composite material sheet deposited with a titanium thin film, the titanium tetrachloride flow rate is 10-20 sccm, the nitrogen flow rate is 50-100 sccm, the hydrogen flow rate is 5-10 sccm, and the deposition temperature is 150-250°C; S4, immersing the pretreated aluminum foil obtained in S1 and the composite material sheet deposited with a titanium thin film obtained in S3 in a self-assembly agent solution with a concentration of 1-5wt%, immersing for 0.5-1h, and drying at 80-100°C to obtain an impregnated aluminum foil and an impregnated composite material sheet, wherein the self-assembly agent solution is selected from an ethanol solution of 3-mercaptopropyltrimethoxysilane; S5. Composite bonding: Place the impregnated aluminum foil and the impregnated composite material sheet in a hot press for 1 to 2 hours to obtain a Ti / Al composite electrode foil, wherein the impregnated aluminum foil is opposite to a side of the impregnated composite material sheet on which a titanium layer is deposited, and the hot pressing temperature is 350 to 450° C. and the pressure is 10 to 20 MPa.
2. The method for manufacturing a Ti / Al composite electrode foil according to claim 1, characterized in that: The cleaning solution includes an ethanol solution and a sodium hydroxide solution, the concentration of the ethanol solution is 50-70wt%, the concentration of the sodium hydroxide solution is 1-3mol / L, and the volume ratio of the ethanol solution to the sodium hydroxide solution is 3:1-5:
1.
3. The method for manufacturing a Ti / Al composite electrode foil according to claim 1, characterized in that: The Ti / Al composite material obtained in step S201 is further processed, specifically including hot isostatic pressing of the Ti / Al composite material: The Ti / Al composite material is placed in a pressure vessel of a hot isostatic pressing device, and the pressure vessel is evacuated to 10 - 3 Pa, and filled with argon to 10 MPa; The hot isostatic pressing equipment is started, the temperature is increased from the initial state of room temperature to the set temperature at a rate of 5-10°C / min, the pressure is increased from the initial state of 10 MPa to the set pressure at a rate of 1 MPa / min, and maintained at the set temperature and set pressure for 0.5-2h, and then the temperature and pressure are reduced to the initial state at the same rate to complete the hot isostatic pressing treatment of the Ti / Al composite material, the set temperature is 500-700°C, and the set pressure is 100-150 MPa.
4. The method for manufacturing a Ti / Al composite electrode foil according to claim 1, characterized in that: The composite material sheet obtained in step S202 is further processed, specifically including: The composite material sheet was cleaned by ultrasonic wave, immersed in a 5-10 wt % dilute hydrochloric acid solution for 5-10 min, rinsed with deionized water, and dried with nitrogen.
5. The method for manufacturing a Ti / Al composite electrode foil according to claim 1, characterized in that: The composite material sheet obtained in step S202 is further processed, specifically including depositing aluminum oxide on the composite material sheet: The composite material sheet is placed in a reaction chamber, the vacuum system is started, and the reaction chamber is evacuated to an initial vacuum degree of 10 - 3 Pa; Using trimethylaluminum and oxygen as reaction gases, turning on the RF plasma source, adjusting the RF power to 250 W, adjusting the pressure in the reaction chamber to 3 Pa, and completing the alumina deposition on the composite material sheet after deposition for 0.5 to 1 hour. The trimethylaluminum flow rate is 5 to 20 sccm, and the oxygen flow rate is 30 to 60 sccm.
6. The method for manufacturing the Ti / Al composite electrode foil according to claim 5, characterized in that: The titanium film is deposited on the side of the composite sheet on which the aluminum oxide is deposited.
7. The method for manufacturing a Ti / Al composite electrode foil according to claim 1, characterized in that: In the step S302, the deposition temperature is increased step by step, the initial deposition temperature is 190-220°C, and the temperature is increased at a rate of 1°C / min until it reaches 250°C.
8. A Ti / Al composite electrode foil, characterized in that: The Ti / Al composite electrode foil is manufactured by the manufacturing method of any one of claims 1 to 7.
9. An electrolytic capacitor, characterized in that: The Ti / Al composite electrode foil according to claim 8 is used as an electrode.
Citation Information
Patent Citations
Preparation method for preparing medium-low pressure composite dielectric film-containing formed foil by surface self-assembly method
CN111768974A
Electrode material for electrolytic capacitor
JP1990260625A